Harry Houdini for kids [ his life and adventures with 21 magic tricks and illusions - Carlson, Laurie W. , 1952- (For kids, 2009)
From Harry Houdini's impoverished childhood to his feat of becoming one of the most successful entertainers of all time, this biography presents a portrait of this magician and escape artist. It